Long-term β-cells autoimmune destruction markers persistence and residual C-peptide secretion in type 1 diabetes mellitus - M. R. Ragimov; O. S. Derevyanko; N. M. Malysheva; Z. T. Zuraeva; L. V. Nikankina; T. V. Nikonova (Сахарный диабет)
Backgraund: It believed that autoimmune process maintained only during the first 5 years of diabetes mellitus type 1 (T1D). Recently scientists discovered the high levels of islet autoantibodies (Ab) in long-standing T1D and some of these patients had residual insulin secretion, determined by the level of C-peptide. According to various sources, the prevalence of such observations ranges from 12 to 48%.Aims: The aim of our study was to assess the duration of autoimmune β-cells destruction markers persistence and residual fasting C-peptide secretion in the long-standing T1D, as well as to determine the possible causes and patterns of these processes.Materials and methods: In the study included 237 patients (91 men, 146 women) with T1D. Patients divided in 4 groups, according to disease duration: а — up to 1 year, n=69 (29%); b — 1–5 years, 52 (22%); c — 5–10 years, 57 (24%); d — more than 10 years, 59 (25%). Ab to glutamic acid decarboxylase (GADA), tyrosine phosphatase-like IA-2 (IA2) and zinc T8 (ZnT8A) were detected by Enzyme Immunoassay. Also detected C-peptide levels and retrospectively HbA1с.Results: Antibodies to antigens of β-cell components were detected in 26 (37%) patients in group A, in 17 patients (33%) in group B, in 15 (29%) in group C and in 14 (23%) — G.In the control group (n = 19), an increased level of antibodies was not revealed. Fasting C-peptide levels were as follows: in group «A» — 0.86 ng / ml [0.53; 1.4], «B» — 0.65 ng / ml [0.27; 0.98], « B «- 0.19 ng / ml [0.17; 0.33],» D «- 0.01 ng / ml [0.01; 0.01]. However, in 13 (22%) patients in group D, fasting C-peptide levels were more than 0.09 ng / ml.Conclusion: The data obtained indicate a long-term persistence of markers of the autoimmune process in patients with T1DM. In groups with a long (more than 5 years) course of T1DM, levels of fasting C-peptide more than 30 pmol/L (0.09 ng / ml or 0.03 nmol / L) were noted in 39 (33.6%) cases.